Flow Dynamics in a Lethal Anterior Communicating Artery Aneurysm - Kerber, Charles W.; Imbesi, Steven G.; Knox, Kim (American Journal of Neuroradiology, 1999)
Summary: We describe and analyze the flow dynamics in replicas of a human anterior communicating artery aneurysm. The replicas were placed in a circuit of pulsating non-Newtonian fluid, and flows were adjusted to replicate human physiologic parameters. Individual slipstreams were opacified with isobaric dyes, and images were recorded on film and by CT/MR angiography. When flow in the afferent (internal carotid) and efferent (anterior and middle cerebral) arteries was bilaterally equal, slipstreams rarely entered the aneurysm. When flow in either the afferent or efferent vessels was not symmetrical, however, slipstreams entered the aneurysm neck, impinged upon the aneurysm dome, and swirled within the aneurysm. Unequal flow in carotid or cerebral systems may be necessary to direct pathologic, fluid slipstreams into an aneurysm.